SAVI Approach Paper 10: Engaging State Governments - SAVI (DFID, 2015)
SAVI as a programme does not directly work with state governments – bu t we work in close conjunction with sister programmes who are supporti ng state governments on governance and sector reforms. SAVI supports n on-government and SHoA partners to play their part in promoting more r esponsive, inclusive and accountable state governance delivering bette r services for citizens....